Characteristics of Arctic winds at CANDAC-PEARL (80 degrees N, 86 degrees W) and Svalbard (78 degrees N, 16 degrees E) for 2006-2009: radar observations and comparisons with the model CMAM-DAS - Hall, Chris; Manson, Alan; Meek, Chris; Xu, X; Aso, Takehiko; Drummond, J. R.; Hocking, W. K.; Tsutsumi, Masaki; Ward, W. E. (Annales Geophysicae, 2011)
Operation of a Meteor Wind Radar (MWR) at Eureka, Ellesmere Island (80° N, 86° W) began in February 2006; this is the location of the Polar Environmental and Atmospheric Research Laboratory (PEARL), operated by the "Canadian Network for the Detection of Atmospheric Change" (CANDAC). The first 36 months of wind data (82–97 km) are here combined with contemporaneous winds from the Meteor Wind Radar at Adventdalen, Svalbard (78° N, 16° E), to provide the first evidence for substantial interannual variability (IAV) of longitudinally spaced observations of mean/background winds and waves at such High Arctic latitudes. The influences of "Sudden Stratospheric Warmings" (SSW) are also apparent. Monthly meridional (north-south, NS) 3-year means for each location/radar demonstrate that winds (82–97 km) differ significantly between Canada and Norway, with winter-equinox values generally northward over Eureka and southward over Svalbard. Using January 2008 as case study, these oppositely directed meridional winds are related to mean positions of the Arctic mesospheric vortex. The vortex is from the Canadian Middle Atmosphere Model, with its Data Assimilation System (CMAM-DAS). The characteristics of "Sudden stratospheric Warmings" SSW in each of the three winters are noted, as well as their uniquely distinctive short-term mesospheric wind disturbances. Comparisons of the mean winds over 36 months at 78 and 80° N, with those within CMAM-DAS, are featured. E.g. for 2007, while both monthly mean EW and NS winds from CMAM/radar are quite similar over Eureka (82–88 km), the modeled autumn-winter NS winds over Svalbard (73–88 km) differ significantly from observations. The latter are southward, and the modeled winds over Svalbard are predominately northward. The mean positions of the winter polar vortex are related to these differences.